3D-QSAR design of novel antiepileptic sulfamides - Gavernet, Luciana (2007)
A three-dimensional quantitative structure-activity relationship method, the comparative molecular field analysis (CoMFA), was applied to design new anticonvulsant symmetric sulfamides. The training set (27 structures) was comprised by traditional and new-generation anticonvulsant (AC) ligands that exhibit a potent activity in MES test. Physicochemical determinants of binding, such as steric and electrostatic properties, were mapped onto the molecular structures of the set, in order to interpret graphically the CoMFA results in terms of field contribution maps. The 3D-QSAR models demonstrate a good ability to predict the activity of the designed compounds (r2 = 0.967, q2 = 0.756).